2013
DOI: 10.1111/acer.12297
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Phase Determines Effects of Repeated Ethanol Vapor Exposure and Withdrawal on Body Temperature and Activity Rhythms of Male Mice

Abstract: The physiological responses of both EtOH exposure and withdrawal differ as a function of time of day. These findings suggest that controlling for the circadian phase of exposure and/or withdrawal may mitigate the severity of symptomatic withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
1
10
2
Order By: Relevance
“…CAF rats show a reduction in nocturnal locomotor activity and withdrawal-induced hypothermia (Taylor et al, 2006). Moreover, core body temperature and locomotor activity are decreased in subjective night during repeated sessions of alcohol vapor intoxication in mice, and there was a trend toward greater hypothermia in mice commencing intoxication during the daytime (Damaggio & Gorman, 2014). In addition, CAF rats show a shift in sleep propensity from the light to dark phase of the LD cycle (Mukherjee & Simasko, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…CAF rats show a reduction in nocturnal locomotor activity and withdrawal-induced hypothermia (Taylor et al, 2006). Moreover, core body temperature and locomotor activity are decreased in subjective night during repeated sessions of alcohol vapor intoxication in mice, and there was a trend toward greater hypothermia in mice commencing intoxication during the daytime (Damaggio & Gorman, 2014). In addition, CAF rats show a shift in sleep propensity from the light to dark phase of the LD cycle (Mukherjee & Simasko, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperthermia is often observed in humans during ethanol withdrawal and it is a risk factor for later development of delirium tremens (Hall & Zador, 1997; Monte et al, 2009). Studies in animal models have shown that either hyperthermia or hypothermia can be shown, depending on the circadian phase (Damaggio et al, 2014a,b). We have also shown disruption of thermoregulation during withdrawal from vapor inhalation (Crawshaw et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…In WD Battery 1, we included body temperature as the last behavior measured (WD Hr 26). We estimated basal body temperature in this experiment one week after the experiment ended, at the same time of day as the temperature assessment during withdrawal, in order to avoid potential circadian confounds (Tankersley et al, 2002; Damaggio et al, 2014a). In WD Batteries 2 and 3, we assessed basal body temperatures 1 to 4 days before placing mice into the vapor inhalation chambers.…”
Section: Methodsmentioning
confidence: 99%
“…Many experimental paradigms have been used for chronic ethanol administration, including daily ethanol injections or intra-gastric lavage, daily ethanol vapor exposure, continuous ad libitum ethanol (5-25%) drinking (either in free-choice or a forced-consumption situation), or fixed interval drinking, with ethanol available at specified times each 24 h (e.g., chronic intermittent drinking, or drinking-in-the-dark). The choice of paradigm used often depends on whether the focus of the study is on regulating the exact amount and/or timing of ethanol administered vs. allowing subjects to control their own ethanol consumption (Kliethermes et al, 2005;Logan et al, 2010;Rosenwasser et al, 2010;Iancu et al, 2013;Pisu et al, 2011;Ahmed, 2012;Damaggio and Gorman, 2013). …”
Section: Evidence Of Ethanol Tolerance In the Scn Circadian Systemmentioning
confidence: 99%